Study on the vacuum freeze-drying of banana and impact on powder properties - Onur Taskin (Case Studies in Thermal Engineering)
This research evaluated vacuum freeze-drying (VFD) for banana slices in terms of drying behavior, energy, cost, color, rehydration, shrinkage, pH and °Brix, microstructure, and thermal images. Additionally, powder properties were investigated. The correlations representing the two-term exponential model constants and their dependence on the VFD parameters indicated that the most appropriate model was Wang & Singh. The drying process took 480 min with 3.967 kWh of energy consumption. Thermal imaging data indicate that the temperature of the products initially decreases before subsequently rising in a continuous manner. The microphotographs illustrated that the dried banana slices had a uniform structure. The pH and color change rate between fresh and freeze-dried slices was quite minimal whereas °Brix values were increased after drying. Furthermore, the dried banana slices demonstrated a high rehydration ratio coupled with minimal shrinkage. The ''100–200 μm'' samples exhibited the lowest values in terms of solubility, wettability, tapped density and bulk density. Further research on the novel freeze-drying assisted methods to improve process efficiency and powder quality is recommended.